Working memory capacity predicts search accuracy for novel as well as repeated targets. Issue 6 (3rd July 2018) - Williams, Lauren H.; Drew, Trafton
ABSTRACT: Visual search behaviour is guided by mental representations of targets that direct attention toward relevant features in the environment. Electrophysiological data suggests these target templates are maintained by visual working memory during search for novel targets and rapidly transfer to long term memory with target repetition. If this account is correct, an individual's working memory capacity should be more predictive of search performance for novel targets than repeated targets. Across six experiments, we tested this hypothesis using both single (Experiments 5 and 6) and multiple (Experiments 1–4) target search tasks with three different types of stimuli (real world objects, letters, and triple conjunction shapes). Each target set was repeated for six consecutive trials. In addition, we estimated visual working memory capacity using a change detection working memory task. Overall, working memory capacity did not predict response time or efficiency in the visual search task. However, working memory capacity was equally predictive of search accuracy for both novel and repeated targets. These results suggest that working memory requirements do not substantially differ between novel and repeated target search, and working memory capacity may continue to play an important role in the encoding or maintenance of target representations after they are presumed to be in long term memory.